Study on the design of the Remote Distance Recording Automation Tool for Regional Water Utility Companies (PDAM) Water Distribution Using WIFI - Ilmi, Ulul; Muiz Pratama, Abdul (Nusantara Publisher, 2024)
Based on the research study on the design of the Remote Distance Recording Automation Tool for PDAM Water Distribution Using WIFI, several conclusions can be drawn. The PDAM water usage recording device, which uses the Water Flow YF-S201 sensor on a microcontroller installed in the PDAM water distribution flow, can accurately read the volume of water flowing through the sensor. Experiments showed that the sensor achieved an average accuracy of 98.9% for water volumes ranging from 1.5 liters to 15 liters. This demonstrates the sensor's high precision in measuring water flow.To build the hardware and software circuit, the ESP8266 WiFi module was used on the atmega328 microcontroller. The data sent to the server via the WiFi network worked as expected as long as it was within the range of the access point. Testing was conducted with a maximum distance of 8 meters, as the WiFi access point device used in the experiment could only reach a maximum of 10 meters and operated at a frequency of 2.4 GHz. This shows that the system can function well within a certain range and supports efficient wireless data transfer.